Análisis de los titulares en medios de comunicación digital del cantón Babahoyo en el primer semestre del 2020 - Ronquillo Palma, Tatiana Petita (2020)
The main purpose of this research is the analysis of the headlines in digital media of the Babahoyo canton in the first semester of 2020. Through the descriptive exploratory research method, digital media was identified as a necessity due to what happens in the news and that this in turn serves so that its citizens are aware of the information that occurs in the locality and in the world, becoming a tool or an indispensable medium when acquiring news. With the study carried out, it was evident that the digital media of the city of Babahoyo are classified as undertakings since they were previously pilot tests. Based on the study carried out, it is concluded that Babahoyo is digital media are useful for its citizens since it is the tool by which they keep in contact with information and at the same time grow more as entrepreneurs and enhance their communication.